Answer:
<h3><u>Let's</u><u> </u><u>understand the concept</u><u>:</u><u>-</u></h3>
Here angle B is 90°
So
and
Are right angled triangle
So we use Pythagoras thereon for solution
<h3><u>Required Answer</u><u>:</u><u>-</u></h3>
perpendicular=p=8cm
Hypontenuse =h =10cm
According to Pythagoras thereon
![{\boxed{\sf b^2=h^2-p^2}}](https://tex.z-dn.net/?f=%7B%5Cboxed%7B%5Csf%20b%5E2%3Dh%5E2-p%5E2%7D%7D)
![\longrightarrow](https://tex.z-dn.net/?f=%5Clongrightarrow)
![\sf b^2=10^2-p^2](https://tex.z-dn.net/?f=%5Csf%20b%5E2%3D10%5E2-p%5E2)
![\longrightarrow](https://tex.z-dn.net/?f=%5Clongrightarrow)
![\sf b={\sqrt {10^2-8^2}}](https://tex.z-dn.net/?f=%5Csf%20b%3D%7B%5Csqrt%20%7B10%5E2-8%5E2%7D%7D)
![\longrightarrow](https://tex.z-dn.net/?f=%5Clongrightarrow)
![\sf b={\sqrt{100-64}}](https://tex.z-dn.net/?f=%5Csf%20b%3D%7B%5Csqrt%7B100-64%7D%7D)
![\longrightarrow](https://tex.z-dn.net/?f=%5Clongrightarrow)
![\bf b={\sqrt {36}}](https://tex.z-dn.net/?f=%5Cbf%20b%3D%7B%5Csqrt%20%7B36%7D%7D)
![\longrightarrow](https://tex.z-dn.net/?f=%5Clongrightarrow)
![\sf b=6](https://tex.z-dn.net/?f=%5Csf%20b%3D6)
![\therefore](https://tex.z-dn.net/?f=%5Ctherefore)
![\overline{BC}=6cm](https://tex.z-dn.net/?f=%5Coverline%7BBC%7D%3D6cm)
![\longrightarrow](https://tex.z-dn.net/?f=%5Clongrightarrow)
![BD=9+6](https://tex.z-dn.net/?f=BD%3D9%2B6)
![\longrightarrow](https://tex.z-dn.net/?f=%5Clongrightarrow)
![BD=15cm](https://tex.z-dn.net/?f=BD%3D15cm%20)
- Now in
![\triangle ABD](https://tex.z-dn.net/?f=%5Ctriangle%20ABD%20)
Perpendicular=p=8cm
Base =b=15cm
- We need to find Hypontenuse =AD(x)
According to Pythagoras thereon
![{\boxed {\sf h^2=p^2+b^2}}](https://tex.z-dn.net/?f=%7B%5Cboxed%20%7B%5Csf%20h%5E2%3Dp%5E2%2Bb%5E2%7D%7D)
![\longrightarrow](https://tex.z-dn.net/?f=%5Clongrightarrow)
![\sf h^2=8^2+15^2](https://tex.z-dn.net/?f=%5Csf%20h%5E2%3D8%5E2%2B15%5E2%20)
![\longrightarrow](https://tex.z-dn.net/?f=%5Clongrightarrow)
![\sf h={\sqrt {8^2+15^2}}](https://tex.z-dn.net/?f=%5Csf%20h%3D%7B%5Csqrt%20%7B8%5E2%2B15%5E2%7D%7D)
![\longrightarrow](https://tex.z-dn.net/?f=%5Clongrightarrow)
![\sf h={\sqrt {64+225}}](https://tex.z-dn.net/?f=%5Csf%20h%3D%7B%5Csqrt%20%7B64%2B225%7D%7D)
![\longrightarrow](https://tex.z-dn.net/?f=%5Clongrightarrow)
![\sf h={\sqrt {289}}](https://tex.z-dn.net/?f=%5Csf%20h%3D%7B%5Csqrt%20%7B289%7D%7D)
![\longrightarrow](https://tex.z-dn.net/?f=%5Clongrightarrow)
![\sf h=17cm](https://tex.z-dn.net/?f=%5Csf%20h%3D17cm%20)
![\therefore](https://tex.z-dn.net/?f=%5Ctherefore)
![{\underline{\boxed{\bf x=17cm}}}](https://tex.z-dn.net/?f=%7B%5Cunderline%7B%5Cboxed%7B%5Cbf%20x%3D17cm%7D%7D%7D)
The hot tub takes in 1,520 watts everyday to keep its water warm. A kilowatt has 1,000 watts (hence kilo means 1,000). 1,520 divided by 1,000 equals 1.520. However, this isn't free electricity - Each kilowatt costs 8 cents or 0.08 of a dollar. 1.520 x 0.08 = 12.160 or $12.16. We aren't done yet! This hot tub runs for 4 months (and we are assuming these months exactly have 30 days each). 4 x 30 = 120. $12.16 x 120 = $1,459.20. In order to keep the hot tub running, you need to pay 1,459.20 for all the kilowatts of electricity it takes.
Answer:
i dont know what level this is
Step-by-step explanation:
C bc i am a professor at Yale and it is simplistic............................................................... <span />
Answer:
The answer is 288
Step-by-step explanation:
I did the assinment